Interaction of Rupture Zones of Adjacent Anchor Plates in an Analogical Medium - Abbad, H.; Meghachou, M.; Dekar, C.; Daoud, S. M. (Engineering, Technology & Applied Science Research, 2013)
In this paper, an experimental study which required the design and implementation of a model containing plastic granules powder to simulate a natural environment, is presented. The latter is subjected to the removal of "anchor plates." For each test, several digital photographs are taken to materialize different deformed configurations during the pullout process. These photos processed in couples by the 7D software (image correlation) giving the evolution of the displacement field and plane strain analogical environment. Particular attention is paid to the discussion of the interference of rupture zones of neighboring anchors by reducing the axis between plates.